Memristor based on amorphous zinc-tin oxide Schottky diodes - Branca, Nuno Miguel de Almeida Casa (2019)
This work reports the fabrication and characterization of metal-insulator-metal (MIM) structures based on Schottky junction between platinum and zinc-tin oxide (ZTO) for memristor application. The devices were produced exclusively by physical vapor deposition methods at room temperature (RT). Before evaluating memory performance, these devices were first characterized in their pristine state as diodes. It was studied how the addition of an intermediate step of oxygen plasma treatment on the platinum surface, as well as the influence of oxide film thickness impact device performance. The produced memristors exhibited a very distinct operation dynamic on the reset process depending on the voltage signal applied in the electroforming process. When the voltage coincides with the forward direction of the diode the reset process runs in gradual analogic way; otherwise the reset process runs in a threshold manner, like the set process in both cases. Oxygen plasma treatment tends to improve the analog mechanism in terms of operation window, regardless of thickness. However, the stability of resistive RAM operation is improved with thicker devices.